Chronic infection by Leishmania amazonensis mediated through MAPK ERK mechanisms - Martinez, Pedro A. (Immunol Res, 2014)
Leishmania amazonensis is an intracellular protozoan parasite responsible for chronic cutaneous leishmaniasis (CL). CL is a neglected tropical disease responsible for infecting millions of people worldwide. L. amazonensis promotes alteration of various signaling pathways that are essential for host cell survival. Specifically, through parasite-mediated phosphorylation of extracellular signal regulated kinase (ERK), L. amazonensis inhibits cell-mediated parasite killing and promotes its own survival by co-opting multiple host cell functions. In this review we highlight Leishmania-host cell signaling alterations focusing on those specific to 1) motor proteins, 2) prevention of NADPH subunit phosphorylation impairing reactive oxygen species production (ROS), and 3) localized endosomal signaling to up-regulate ERK phosphorylation. This review will focus upon mechanisms and possible explanations as to how Leishmania spp. evades the various layers of defense employed by the host immune response.